Bangladesh's Approach towards International Criminal Law: A Case Study of International Crimes Tribunal Bangladesh - Fazi, Abdullah; Tehrani, P.; Ahmed M.; Shah S. (Canadian Center of Science and Education, 2019)
The International Crimes Tribunal Bangladesh that has been found by the Bangladeshi Government to try war crimes during India Pakistan war of 1971. The tribunal is violating the fair trial rights as guaranteed by Constitution, the International Covenant on Civil and Political Rights and International Humanitarian Law and the standard of the International Crimes Tribunal Bangladesh is far below than that setup by The International Criminal Tribunal for the former Yugoslavia, the International Criminal Tribunal for Rwanda and the International Criminal Court. These irregularities imply serious concern over the proceedings of the said tribunal. Study seeks to describe the International Law about war crimes particularly with respect to fair trial provisions and it compare the proceedings of the Bangladeshi tribunal with the other internationally recognized tribunals.